Catalytic effect of MoS2 on hydrogen storage thermodynamics and kinetics of an as-milled YMg11Ni alloy. Issue 60 (31st July 2017) - Zhang, Yanghuan; Ji, Meng; Yuan, Zeming; Bu, Wengang; Qi, Yan; Guo, Shihai
Abstract : MoS2 nanoparticles embedded into alloys markedly enhance the dehydrogenation performance, such as lowering dehydrogenation temperature and enhancing dehydrogenation rate. Abstract : In this study, YMg11 Ni and YMg11 Ni + 5 wt% MoS2 (named YMg11 Ni–5MoS2 ) alloys were prepared by mechanical milling to examine the effect of adding MoS2 on the hydrogen storage performance of a Y–Mg–Ni-based alloy. The as-cast and milled alloys were tested to identify their structures by X-ray diffraction and transmission electron microscopy. The isothermal hydrogen storage thermodynamics and dynamics were identified through an automatic Sieverts apparatus, and the non-isothermal dehydrogenation performance was investigated by thermogravimetry and differential scanning calorimetry. The dehydrogenation activation energy was calculated by both Arrhenius and Kissinger methods. Results revealed that adding MoS2 produces a very slight effect on hydrogen storage thermodynamics but causes an obvious reduction in the hydrogen sorption and desorption capacities because of the deadweight of MoS2 . The addition of MoS2 significantly enhances the dehydrogenation performance of the alloy, such as lowering dehydrogenation temperature and enhancing dehydrogenation rate. Specifically, the initial desorption temperature of the alloy hydride lowers from 549.8 K to 525.8 K. The time required to desorb hydrogen at 3 wt% H2 is 1106, 456, 363, and 180 s corresponding to hydrogen desorption temperatures at 593, 613, 633, and 653 K for the YMg11 Ni alloy, and 507, 208, 125, and 86 s at identical conditions for the YMg11 Ni–5MoS2 alloy. The dehydrogenation activation energy ( E a ) values with and without added MoS2 are 85.32 and 98.01 kJ mol −1 . Thus, a decrease in E a value by 12.69 kJ mol −1 occurs and is responsible for the amelioration of the hydrogen desorption dynamics by adding a MoS2 catalyst.